2017
DOI: 10.1186/s13030-017-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

Tolerable pain reduces gastric fundal accommodation and gastric motility in healthy subjects: a crossover ultrasonographic study

Abstract: BackgroundObstacles to pain management include patients’ reluctance to inform healthcare provides about their pain, and differences in the pain management aims between patients and healthcare providers. The objective of this study was to evaluate whether tolerable pain influences gastric fundal accommodation and gastric motility in healthy subjects.MethodsWe undertook a crossover comparison study to evaluate gastric fundal accommodation and gastric motility in 74 healthy subjects in the presence or absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Interestingly, although anaesthesia duration had no influence on PAC rate, horses anesthetized for diagnostic imaging purposes had a significantly lower PAC rate (6.5%) than horses undergoing surgery (16.7% PAC) and horses receiving no opioids postoperatively had a higher PAC (14%) rate than horses receiving butorphanol (5.3%), underscoring the importance of postoperative pain management. Pain initiates a spinal reflex arc, increases sympathetic activity and cortisol and endogenous opioid release, thus inhibiting propulsive gastrointestinal motility (66)(67)(68)(69). Effective pain management is thus crucial to ensure patients' welfare and minimize postoperative morbidity and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although anaesthesia duration had no influence on PAC rate, horses anesthetized for diagnostic imaging purposes had a significantly lower PAC rate (6.5%) than horses undergoing surgery (16.7% PAC) and horses receiving no opioids postoperatively had a higher PAC (14%) rate than horses receiving butorphanol (5.3%), underscoring the importance of postoperative pain management. Pain initiates a spinal reflex arc, increases sympathetic activity and cortisol and endogenous opioid release, thus inhibiting propulsive gastrointestinal motility (66)(67)(68)(69). Effective pain management is thus crucial to ensure patients' welfare and minimize postoperative morbidity and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Self-report questionnaire to evaluate alexisomia Each participant was evaluated for potential alexisomic symptoms using the Shitsu-Taikan-Sho Scale (STSS total), a self-report questionnaire consisting of 23 items rated on a scale of 1 to 5, which provides a total score ranging between 23 and 115 (2,6). The STSS total includes the scores on three subcategories: difficulty identifying bodily feelings (DIB), OA, and LHM based on bodily feelings.…”
Section: Methodsmentioning
confidence: 99%
“…TrP diagnosis requires careful manual examination and reliability estimates were generally higher for subjective signs such as tenderness (19). Based on a previous study, palpation was performed when each participant was in a relaxed prone position lying on a bed (6,20). The palpation area was approximately 3 cm wide (horizontal) and 2 cm high (vertical).…”
Section: Ltrp Palpation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Research evidence has shown that untreated pain in the early stages of life can lead to devastating effects, which may be short or long term. These effects may be physiological, developmental, emotional, or behavioural and may persist into the later stages of life (Deere et al, 2012;Friedrichsdorf et al, 2015;Hasuo et al, 2017;King et al, 2011;Mathews, 2011). Untreated pediatric pain has been linked with functional disability, longer duration of hospitalization, poor life quality (Friedrichsdorf et al, 2015), and development of chronic pain (Sessle, 2011), which becomes burdensome to affected children, their families, and societies (Bushnell, Čeko, & Low, 2013;Dueñas, Ojeda, Salazar, Mico, & Failde, 2016).…”
Section: Introductionmentioning
confidence: 99%